Choosing the right strategies: An analysis of crisis response strategies in Chinese universities. - Yongshi Liu; Deyi Gao; Hongtao Duan (PLoS ONE)
Situational Crisis Communication Theory (SCCT) provides a theoretical framework for crisis response strategies in different crisis situations. Based on the theoretical framework of SCCT, a qualitative thematic analysis is conducted to examine the crisis response strategies used in 182 response documents officially released by Chinese universities, and a content analysis is further employed to classify 147 crises in 125 universities into three clusters to examine the use of strategies in addressing different types of crises. The findings revealed that Chinese universities have adopted 17 new strategies beyond the strategies proposed by SCCT, highlighting a discrepancy between the theoretical ground of the theory and the application of strategies in real-life crisis response of Chinese universities. Furthermore, the results revealed the applicable strategies for different crisis clusters, which contributed to construct the framework of crisis response strategies for Chinese universities in different situations. This study expanded SCCT theoretically by enriching the crisis response strategies while practically improving the applicability of SCCT in Chinese universities. The findings provided guiding significance for Chinese universities administrators in developing and implementing effective crisis response strategies in real-life crisis situations, enabling them to adjust and optimize their plans by incorporating innovative strategies to enhance the effectiveness of responses. These innovative strategies also provided empirical evidence for other organizations in different cultural contexts in crisis response.